Microscopic features of tick-bite lesions in anteaters and armadillos - Emas National Park and the Pantanal region of Brazil - Silva, MFL; Szabo, MPJ (New York Acad Sciences, 2004)
The naturally occurring wildlife host associations between ticks and tick-borne pathogens found in the neotropics are poorly described. Understanding tick-bite lesions is important as these are the site of host reaction to and pathogen delivery by ticks. As part of a comprehensive study concerning established and emerging tick-host relationships. The present work describes some aspects of tick-bite lesions in anteaters and armadillos captured at the Emas National Park and the Pantanal region of Brazil. Biopsies were of skin were taken and examine. Tick feeding sites of all animals displayed an eosinophilic homogeneous mass, the cement cone, and, occasionally, a feeding cavity underneath the tick attachment site. At these locations the epidermis was usually thickened due to keratinocyte hyperplasia. The main dermal changes included tissue infiltration with a varying number of inflammatory cells, edema, hemorrhage. and vascular dilatation. Cellular infiltration of the dermis was predominantly composed of mononuclear cells, neutrophils. and eosinophils. Mast cells were also seen in both non-parasitized and parasitized skin but were found in higher numbers at perivascular sites and in parasitized skin. Basophils were not seen at tick attachment sites of anteaters or armadillos.
Keywords: anteaters; Myrmecophaga tridactyla; armadillo; Euphractus sexcinctus; Ticks; histopathology